The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1097/01.mlr.0000245181.96133.db
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item Functioning (DIF) and the Mini-Mental State Examination (MMSE)

Abstract: The examination of item bias in cognitive impairment assessment instruments has practical and theoretical implications in the context of health disparities. Considerable DIF has been identified in the MMSE. A critical factor that may contribute to measurement bias is language translation and conversion. Once DIF has been established consistently in a measure, decisions regarding adjustments proceed. Perhaps the development of guidelines for appropriate adjustments for DIF correction in self-reported measures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 47 publications
3
74
1
2
Order By: Relevance
“…The CAREDIAG has been studied using several advanced psychometric models, including analyses of its relationship to dementia diagnosis 38,39 and performance across ethnically diverse groups. 40,41 The α C for this sample was 0.875. The Observed Total Behavior Disorder Index was also used to measure observed behaviors.…”
Section: Interview Instrumentsmentioning
confidence: 99%
“…The CAREDIAG has been studied using several advanced psychometric models, including analyses of its relationship to dementia diagnosis 38,39 and performance across ethnically diverse groups. 40,41 The α C for this sample was 0.875. The Observed Total Behavior Disorder Index was also used to measure observed behaviors.…”
Section: Interview Instrumentsmentioning
confidence: 99%
“…The total score possible for the test is 30. Ramirez et al 10 found that the Flesch Reading Ease Index was 86. 4 …”
Section: Item Structure Of the Original Mmsementioning
confidence: 99%
“…While Folstein et al 1 suggested that there were 11 categories covered in the MMSE, Tombaugh and McIntyre 7 said that [43][44][45][46] The point here is that the MMSE is not unidimensional, 42 which a total score seems to suggest. Furthermore, Ramirez et al 10 found using a differential item functioning (DIF) analysis that different items performed differently for different groups tested. Lopez et al 42 agreed many items were classified as ''too easy'' in their item analysis.…”
Section: Advantages and Disadvantages Of The Mmsementioning
confidence: 99%
See 1 more Smart Citation
“…Education levels significantly influenced the performance on individual MMSE items which confirms earlier research on the differential item performance attributable to education, race, ethnicity and language, and its use in educationally disadvantaged populations has been questioned. 69 Given the significantly poorer performance of participants with lower education levels on the recommended attention/concentration item the alternate item would preferred for local MMSE administration. Performance on the SIS was not significantly associated with education (p=.578) suggesting that this subset of MMSE items are less influenced by education effects and that it could be a useful alternative to the MMSE locally.…”
Section: Influence Of Demographic Variables and Depressionmentioning
confidence: 99%